A Comprehensive Literature Review of Treatment of Psoriasis in Patients With Psoriatic Arthritis - Amalia Dwi, Amalia Dwi; Regina, Regina; Callista, Callista (International Medical Journal Corp. Ltd, 2024)
Background: The treatment of psoriasis in patients with psoriatic arthritis (PsA) is a multifaceted challenge that necessitates a comprehensive understanding of the interplay between skin and joint manifestations of the disease, as well as the associated comorbidities. The literature on this topic reveals a progressive evolution in the therapeutic landscape and highlights the complexity of managing PsA effectively. Literature Review: Kingsley and Scott (2015) highlighted the effectiveness of synthetic and biologic disease-modifying antirheumatic drugs (DMARDs) in treating PsA, noting that effective management requires addressing both skin and joint symptoms (H Kingsley & L Scott, 2015). De Marco et al. (2020) explored non-topical treatments for early, untreated psoriatic disease, revealing that while certain pharmacological interventions like apremilast and biologics show promise, there remains a lack of comprehensive composite indices as primary outcome measures. The influence of comorbid conditions on drug choice was further elaborated by Ritchlin et al. (2020), who emphasized the importance of personalized treatment plans tailored to the severity of PsA and the presence of comorbidities (J Mease et al., 2019). Conclusion: In conclusion, the treatment of psoriasis in patients with psoriatic arthritis requires a multifaceted approach that integrates both dermatological and rheumatological considerations, while also addressing the complexities introduced by comorbidities. The literature emphasizes the importance of individualized treatment plans and highlights the need for ongoing research to better understand the interplay between skin and joint symptoms, ultimately aiming for improved patient outcomes.